SCAT3 assessment of non-head injured and head injured athletes competing in a large international youth soccer tournament. Issue 4 (2nd October 2017) - Gorman, Matthew; Hecht, Suzanne; Samborski, Andrew; Lunos, Scott; Elias, Steven; Stovitz, Steven D.
ABSTRACT: To our knowledge, no study has evaluated Sideline Concussion Assessment Tool −3rd Edition (SCAT3) scores during competition in athletes who have not had a head injury. The purpose of our pilot study was to compare SCAT3 scores in non-injured (NI), injured (but not head injured) (I), and head injured (HI) youth soccer players during competition and to establish preliminary baseline data for non-head injured athletes in a competitive setting. The HI group demonstrated significantly more symptoms ( M  = 9.7, SE = 0.8) than the I and NI (3.3, SE = 1.2, and 3.2, SE = 0.7, respectively) groups. The HI group also demonstrated a significantly higher symptom severity score (25.3, SE = 2.8) than the I and NI groups (7.7, SE = 4.1, and 5.9, SE = 2.5, respectively). There were no statistically significant differences in mean total Standardized Assessment of Concussion (SAC) scores and mean subsection SAC scores between the groups. Clinicians should also be aware that non-injured in-competition athletes may report more symptoms on the SCAT3 than those evaluated in a non-competition setting.